الشباب وثقافة المدرسية في الجزائر دراسة ميدانية لتلاميذ المدارس الثانوية - ميسوم, غشام; بلحاج, حسنية (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة تحليل ما الذي غير في علاقة الأجيال الشابة مع المدرسة. وقد بينا أنه بدءا من اللحظة التي أصبحت فيها المدرسة لكافة التلاميذ تغيرت العلاقة، نتيجة إدخال ثقافة الشباب للمدرسة، المتمثلة في اللباس واللغة والصورة والصوت التي يلتزم بها الشباب الثانويين تعتبر تهديدا كبيرا للثقافة المدرسية، وهذا باعتماد سلم احتجاجي يقوم على الرفض والعنف. في خضم ذلك يخرج التعليم والنجاح المدرسي من المدرسة، وعمل الانتقاء يتم خارجها. باستخدام السلع التعليمية: سواء السلع العامة (اختيار المدرسة) وخدمات السوق (الدروس الخصوصية) والسلع السوقية (المنتجات التعليمية ، الأدوات الرقمية). فتحت مزيجا من تقنيات البحث الكمي والنوعي حاولنا اختبار فرضيات البحث:الملاحظة في عين المكان بصفتي منخرط فعلى في الثانوية. ثم اخترت العمل في مدرستين ثانويتين في غليزان، داخلهما استرجعت358استمارة، ثم قابلت ثلاثون تلميذا في مجموعة بؤرية في كل منها خمسة عشر تلميذ ، ثم استخدام أنواع أخرى مقابلات حرة مع عشرون مدرسا ومقابلات حرة مدراء المؤسسات والمساعدين التربويين وأولياء التلاميذ. Abstract: This study aims to analyze what changed the relationship of the young generations with the school. Starting from the moment when the school became for all students, the youth culture was introduced to the school, accompanied by the exit of education. Success became playing outside its walls, all of that changed the issues of the school and the relationship with it. My central concern will be the study of some forms of youth culture and how they overlap with school culture, and the impact of students working outside the school for school success in their impact on the school institution. I opened a mixture of quantitative and qualitative research techniques. We used a set of field procedures to test the research hypotheses: On-the-spot observation as an actual high school student. Then I chose to work in two secondary schools in Relizane. Within 358 questionnaires were retrieved. Then, I interviewed thirty students in a focus group, each of which had fifteen students in each institution. Other types were used: free interviews with twenty teachers and free interviews with directors of institutions, educational assistants and parents of students
Youth and school culture in Algeria -A field study for secondary school students
مقال
Keywords: الثقافة المدرسية ، ثقافة الشباب، الثقافة الرقمية، العنف المدرسي، الغش المدرسي، النجاح المدرسي، الدروس لخصوصية.; school culture, youth culture, digital culture , school violence, school cheating, school success, private lesson